Africa Quaker Archives: A Short Report for Quaker Studies - Collea, Beth (Quaker studies, 2023)
The Africa Quaker Archives at Friends Theological College in Kaimosi, Kenya, was founded in partnership with the Quaker Religious Education Collaborative (QREC) in 2020 as a centre for all of African Quakerism. It began with the explicit hope that collection, preservation and study of materials about the earlier years of African Quakerism could enrich work in religious education and improve recordkeeping practices for Quaker meetings for business. It is already achieving both objectives and inspiring the world family of Friends with its grassroots Oral Histories of Quaker Faith project.